Review of FROST-ARNOLD, K. (2023) Who Should We Be Online? A Social Epistemology for the Internet New York: Oxford University Press - Jordá, Beatriz (Daimon Revista Internacional de Filosofia, 2024)
Reseña del libro Who Should We Be Online? A Social Epistemology for the Internet